Atypical Maisonneuve’s Fracture: A Case Report - Alwi Rachman; Respati Suryanto Dradjat (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: A Maisonneuve’s Fracture is a fracture of proximal third fibula associated with a disruption of the distal tibiofibular syndesmosis, the interosseous membrane and associated injuries (eg, fracture of the medial malleolus, fracture of the posterior malleolus, and rupture of the deltoid ligament). The mechanism for the fracture is an external rotation force to the ankle with transmission of the force through the interosseous membrane which causes a proximal fibular fracture.In a very rare form, we can found an unusual pattern of the level of the involved fibula, such as middle third of fibula. A 19 year old male presented to us with pain and swelling of his left ankle after felt while playing futsal. Physical examination showed deformity, swelling and tenderness on his left ankle. Range of motion was decreased. On imaging, plain radiographs of left ankle showed dislocation of the ankle, with disruption of syndesmotic and fracture comminutive middle third of fibula. We performed operation which are consists of three procedures; closed reduction, percutaneous fixation of syndesmotic by using a single transfixing screw, and plate-screw for the fibula. Normal range of motion is achieved well after 8 weeks, without pain on full weightbearing. The pattern of the fracture-dislocation of the ankle discussed is very rare. The mechanism of the injury is a twisting motion of the upperbody inward, while the foot is planted, resulting a more higher energy impacted to the ankle and fibula. We performed closed reduction easily by reverse the mechanism of injury. Keywords: Maisonneuve’s Fracture, distal tibiofibular syndesmosis, interosseous membrane, rupture of the deltoid ligament